Methods for assessing muscle strength in older adults diagnosed with COVID-19: an integrative review - Regis, Jerônimo de Freitas; Chaves, Érika Almeida; Santos, Denis Carlos dos; Oliveira, Márcio Rogério de; Gil, André Wilson de Oliveira (JRG Journal of Academic Studies, 2024)
This study aimed to analyze the evidence available in the scientific literature on the methods used to assess the muscle strength of elderly people affected by COVID-19 who participated in rehabilitation during hospitalization or after hospital discharge. The integrative review was used as a research method, as this type of review allows the systematization of studies with different methodologies (experimental and non-experimental). Four different methods were found to assess the muscle strength of elderly people with COVID-19: hand grip strength, MRC scale, static squat and 1RM test. Our findings indicate that the choice of methods should be based on the critical analysis of the health professional, observing the patient's state of health and the proposed intervention. The methods must be applied in a standardized way for their correct classification based on the reference values and/or monitoring of the patient's evolution throughout the intervention with physical exercises.